Study on the space-time distribution and sustainable development of wetland ecotourism resources in Shandong Province. Issue 1 (November 2020) - Liu, Xiaomei; Wang, Hui; Zhao, Weijun; Yan, Tingting; Liu, Boying
Abstract: Wetland, ocean, and forest are regarded as the world's three major systems. Among them, wetland has always been regarded as one of the signs of sustainable development of urban ecological environment. Therefore, its ecological problems, rational development and protection have become the focus of the sustainable development of wetlands and even cities. This study took wetlands in 17 cities in Shandong Province as the research object, then collected relevant data on the area of various types of wetlands in Shandong Province in 2008 and 2013 and analyzed the changing trend of wetland area in Shandong Province in recent 5 years by using methods including multivariate statistics and GIS space analysis, and raised some ecological problems at the same time. The results showed that: 1) In terms of time, the wetland area in Shandong Province has been reducing in the past five years. Compared with 2008, the wetland area in Shandong Province decreased by 24.57% in 2013; 2) In terms of space, the wetland area in coastal areas was seriously degraded, with a reduction rate of more than 50%; 3) In terms of wetland types, natural wetlands such as lakes and rivers were decreasing year by year. They have respectively reduced by 1.02×105 hectares and 4.21×105 hectares while the artificial wetland has increased by 5.33×105 hectares, which means some natural wetlands have been converted into artificial wetlands. The most obvious was the construction of wetland parks; 4) There were a series of ecological problems in the wetlands in Shandong Province, such as blind reclamation and deterioration of the quality of water resources.